THE RISK FACTORS OF PESTICIDES EXPOSURE IN THE PRESENCE OF PESTICIDE METABOLITES IN CHILDREN'S URINE THAT IS LIVING IN THE BREBES REGENCY AGRICULTURAL AREA, INDONESIA - ilyas - ibrahim (FORIKES, 2022)
Pesticides are toxic chemicals that can interfere with health and the environment. Exposure to pesticides endangers human health because pesticide residues accumulate in agricultural products and the surrounding environment.Effects of pesticides on human health, especially children can affect the process of growth and development. The purpose of this study was to analyze the history of pesticide exposure in the presence of pesticide metabolites in the urine of children.Type of this study was observational analytic with cross sectional design. The independent variables were history of pesticide exposure and dependent variable, the presence of pesticide metabolite in child urine.Research subjects were elementary school students in Brebes region as many as 48 students, using total sampling in grade 4 students in 2 elementary schools of Bulakamba sub-district Data collection was done by interview, observation and urine metabolite examination.Chi square was used for data analysis. The results showed that there was a relationship between parent's job (p=0.023, OR = 3.053), children's involvement in agricultural activities (p=0,001, OR=4,400), student's habits of playing in agricultural area (p=0,002; OR=4,583). The presence of pesticides in the home environment (p=0.013; OR=3,536), drinking water source (p=0.008; OR=8,400) in the presence of pesticide metabolites in studentsThus, there is a relationship between the history of exposure to pesticides with the presence of pesticide metabolites in the urine of students.